2013
DOI: 10.1038/srep02936
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enhanced Raman Scattering of Graphene using Plasmonic Nano-Structure

Abstract: Highly enhanced Raman scattering of graphene on a plasmonic nano-structure platform is demonstrated. The plasmonic platform consists of silver nano-structures in a periodic array on top of a gold mirror. The gold mirror is used to move the hot spot to the top surface of the silver nano-structures, where the graphene is located. Two different nano-structures, ring and crescent, are studied. The actual Raman intensity is enhanced by a factor of 890 for the G-peak of graphene on crescents as compared to graphene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…The effectiveness of plasmonic nanostructures to enhance Raman scattering in graphene has been recently demonstrated by utilizing metal nanoparticles and patterned nanostructures on or in close proximity of a graphene sheet [16][17][18][19][20][21][22][23][24]. While reports of large Raman enhancement factors are abundant in the literature, nonetheless, little work has been done on distinguishing resonant pump absorption from resonant Stokes emission and investigating the peculiar effects of each individual mechanism on the Raman spectrum of graphene.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of plasmonic nanostructures to enhance Raman scattering in graphene has been recently demonstrated by utilizing metal nanoparticles and patterned nanostructures on or in close proximity of a graphene sheet [16][17][18][19][20][21][22][23][24]. While reports of large Raman enhancement factors are abundant in the literature, nonetheless, little work has been done on distinguishing resonant pump absorption from resonant Stokes emission and investigating the peculiar effects of each individual mechanism on the Raman spectrum of graphene.…”
Section: Introductionmentioning
confidence: 99%
“…Khorasaninejad et al [145] experimentally found that Raman scattering intensity is enhanced by a factor of approximately 900 when graphene is put on top of silver plasmonic nanostructures. Smirnova et al [146] designed gold metamaterial structures placed on top of graphene to excite the asymmetric Fano resonance modes that enhance second-harmonic generation in graphene.…”
Section: (B) Enhancement Of Nonlinearities Through Graphene Nanostrucmentioning
confidence: 99%
“…As reported by several authors previously, the enhancement of a particular Raman mode of graphene depends on the excitation energy of the laser and plasmonic characteristics of the metallic structure in contact with the graphene, and consequently, the enhancement factors for the D, D', G, and 2D modes can be very different. [7,8] Moreover, not only the kind of metal but also the shape, dimensions, and mutual geometry of the metallic structure and graphene are of utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…As reported by several authors previously, the enhancement of a particular Raman mode of graphene depends on the excitation energy of the laser and plasmonic characteristics of the metallic structure in contact with the graphene, and consequently, the enhancement factors for the D, D', G, and 2D modes can be very different. [7,8] Moreover, not only the kind of metal but also the shape, dimensions, and mutual geometry of the metallic structure and graphene are of utmost importance.In a typical experiment, the enhancement of the Raman signal can be achieved by deposition of a thin layer of silver or gold or their nanoparticles over the graphene. This geometry, however, reduces intensity of the incoming light, and also, the scattered light is partly absorbed by the metal.…”
mentioning
confidence: 99%